Wernicke’s encephalopathy In a Rural Tertiary Teaching Hospital: A Case Report - Dr.Shaik Fathimunni; Dr.Uma MA; Dr.Karthik; Dr. Oersala Thasneem ara (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Wernicke’s encephalopathy is a neurologic disorder caused by thiamine (vitamin B1) deficiency, often associated with chronic alcoholism, malnutrition, or other conditions that impair thiamine absorption or utilization. It presents with a classic triad of confusion, ataxia, and ophthalmoplegia, but the full triad is rarely present in all cases. Case Presentation: We report a case of Wernicke’s encephalopathy in a 50-year-old male who presented with acute onset of confusion, unsteady gait, and blurred vision. His medical history was significant for chronic alcohol use and poor dietary intake. He was admitted to our rural tertiary hospital for evaluation and management. Conclusion: Early recognition and prompt thiamine administration are critical for improving outcomes in patients with Wernicke’s encephalopathy, especially in resource-limited settings.